A Court’s Right to Moderate Administrative Penalty in Selected Central European Countries - Nikolaj Zakrenicnyj (Central European Public Administration Review)
The purpose of this paper is to analyse the extent of a court’s authority to moderate[1] penalties imposed by administrative bodies in several Central European countries: the Czech Republic, Slovakia, Germany, and Austria. The central goal is to investigate the legal frameworks within these nations and their relationship to Article 6 of the European Convention on Human Rights. The methodology employed involves a comparative analysis of legal provisions in the aforementioned countries concerning judicial review of administrative penalties. The study scrutinizes the differences in the legal approaches taken by these nations, highlighting the diverse methods used to address the court’s role in moderating administrative penalties. The investigation is grounded in the concept of full jurisdiction, emphasising the right of individuals to have their cases thoroughly examined by a court, which also includes assessing the legality, merit, appropriateness, and proportionality of the penalties imposed. The findings reveal significant variations among the surveyed countries regarding the approach to judicial review of administrative penalties. These differences underscore the complex interplay between the executive and judiciary branches within legal systems, raising crucial concerns about principles such as legal certainty, proportionality, and the right to an effective remedy. The paper illuminates the varying degrees of court intervention in moderating administrative penalties across different legal contexts and makes a substantial academic contribution by shedding light on a relatively understudied aspect of administrative law within Central Europe. It provides valuable insights into how different legal systems address the delicate balance between executive power and judicial oversight, particularly in matters of administrative penalties. The study’s originality lies in its comparative approach, offering a nuanced understanding of the court’s role in moderating penalties and its implications for broader legal principles and human rights protection. Furthermore, the paper serves as a foundational resource for scholars and practitioners interested in exploring the origins and nuances of judicial moderation in administrative law, potentially inspiring further research and providing a schematic tool for navigating this complex legal terrain.